Biopiracy: Abolish Corporate Hijacking of Indigenous Medicinal Entities - Imran, Yoonus (ScientificWorldJournal, 2021)
Biopiracy as “a silent disease” is hardly detectable because it does not leave traces frequently. The corporate hijacking of food is the most important health hazard in this era; giant commercial enterprises are using intellectual property rights to patent indigenous medicinal plants, seeds, genetic resources, and traditional medicines. The new era of biotechnology relies on the genes of living organisms as raw materials. The “Gene Rush” has thus become similar to that of the old “Gold Rush.” Sri Lanka has been spotted in the top 34 biodiversity hotspots globally. Moreover, localized in the tropics, human generations in Sri Lanka have utilized the array of plant species for herbal treatments and treatment of diseases. Sri Lanka after its 30-year civil war is moving towards a solid growth and conservation of the environment which is a major component in a sustainable development where the conservation of biodiversity plays a significant role. In this paper, we present an overview of typical cases of global biopiracy, bioprospecting via introduction of cost-effective deoxyribonucleic acid (DNA) fingerprinting and international protocol with Private-Public-People Partnership concept as excellent forms of utilization of natural resources. We propose certain perspectives as scientists towards abolishing biopiracy and also to foster the fair utilization of natural resources; since the economy of most developing countries is agriculture based, the gross domestic product of the developing countries could be increased by enhanced bioprospecting via introduction of cost-effective DNA fingerprinting technologies and thus not being a pray of corporate hijacking.“Biopiracy is biological theft; illegal collection of indigenous plants by corporations who patent them for their own use” (Vandana Shiva).